The Influence of Brand Image, Experiential Marketing and Word Of Mouth on Purchase Decisions at E-Commerce Shopee in Sidoarjo: Pengaruh Brand Image, Experiential Marketing dan Word Of Mouth terhadap Keputusan Pembelian pada E-Commerce Shopee di Sidoarjo - Wildan Nasution; Dewi Komala Sari (Academia Open, 2021)
This study aims to determine the effect of brand image, experiential marketing and word of mouth on purchasing decisions at Shopee e-commerce in Sidoarjo. The method used in this research is a quantitative approach method. Sampling in this study was carried out using a probability sampling method with the type of proportionate stratified random sampling with a total of 100 respondents who had purchased products through the Shopee e-commerce online shopping application in Sidoarjo. The data analysis technique used in this study uses multiple linear regression using the SPSS Statistics version 25 program. The results of this study prove that brand image affects purchasing decisions, experiential marketing affects purchasing decisions, word of mouth affects purchasing decisions.